Association between atherogenic index of plasma and coronary lesion severity in NSTEMI patients - Nasution, Umi Hazzar; Sitepu , Andika; Haykal, Teuku Bob; Siregar, Yasmine; Lubis, Hilfan Ade Putra; Ketaren, Andre Pasha; Hasan, Harris (Heart Science Journal, 2026)
Background: Early identification of the severity of coronary lesions is very important to determine the appropriate management strategy, especially in patients with non-ST-elevation myocardial infarction (NSTEMI). Objective: This study aimed to determine the relationship between the Atherogenic Index of Plasma (AIP) and the severity of coronary lesions in NSTEMI patients. Methods: This study was an analytical observational cross-sectional design conducted at Haji Adam Malik Hospital, Medan, in 2023. Data were collected from medical records of NSTEMI patients and coronary angiography results. Statistical analysis was performed to assess the relationship between AIP and the severity of coronary lesions, including bivariate tests and multivariate logistic regression. Result: A total of 101 NSTEMI patients were included in this study. AIP values were significantly higher in patients with moderate to severe coronary lesions compared to those with mild lesions. An AIP ≥ 0.434 showed a sensitivity of 64.1% and specificity of 67.6% in predicting moderate to severe lesions. Multivariate analysis showed that AIP was the strongest independent predictor of coronary lesion severity, along with age, diabetes mellitus, and ejection fraction. Conclusion: AIP is significantly associated with the severity of coronary lesions in NSTEMI patients and can be used as a simple yet effective risk indicator.